Diabetic Foot: Clinical Presentations and Management Outcome - Biswas, Suttam Kumar; Roy, Shilpi Rani; Sarker, Subbrata; Biplob, Md Mustafizur Rahman; Delta, Md Mustafizur Rahman; Rahman, Md Mizanur; Paul, Arup Roton; Saha, Moloy Kumar (Community Based Medical Journal, 2017)
The diabetic foot, the foot of diabetic patients with ulceration, infection and/ or destruction of the deep tissues associated with neurological abnormalities and various degrees of peripheral vascular disease in the lower limb is quite common. A descriptive, cross-sectional study was carried out with an objective of assessing the common presentations and management outcome of diabetic foot. The study was carried out in the Surgery Department of Mymensingh Medical College Hospital, Mymensingh with a conveniently selected 130 patients of diabetic foot according to inclusion and exclusion criteria. The study period was one year. Out of 130 cases, the highest number of patients 55(42.4%) were in age group 50 to 59 years with a mean age of 60.1 years and standard deviation (SD) of 9.8 years. Majority of the patients 91(70.0%) were male. Of them, 83(91.2%) were smokers. Of 130, 51(39.2%) patients were illiterate and 41(31.5%) were farmer. Majority 67(51.53%) patients had history of uncontrolled diabetes for 10-15 years. Most of the patients, 97(74.6%) were presented with neuropathic ulcer, whereas 24(18.4%) ischemic ulcers and 9(7.0%) were infective ulcers, and majority of the lesions 49(37.7%) were located on toes. Highest number of patients, 44(33.8%) were treated conservatively, while 37(28.4%) were treated by debridement, dressing and resurfacing, 17(13.1%) were treated by incision and drainage, and 32(24.6%) patients were treated by amputation. Most of the patients, 108(83.1%) were cured, of them, 36(33.3%) were treated conservatively, while 31(28.7%) by debridement and dressing, 17(15.7%) were treated by toe disarticulation, 13(12.0%) by incision and drainage, 4(3.7%) by above knee amputation, 4(3.7%) by ray amputation and 3(2.8%) by below knee amputation. Illiterate male smokers in their 6th and 7th decades of life with uncontrolled diabetes are the victim of diabetic foot. Neuropathy, vasculopathy, infections and trauma are identified risk factors. Conservative treatment, debridement and dressing, off-loading, culture-guided antibiotics therapy and amputations are the most successful modalities. CBMJ 2017 July: Vol. 06 No. 02 P: 25-31